2010
DOI: 10.1093/carcin/bgq212
|View full text |Cite
|
Sign up to set email alerts
|

Inducible COX-2-dependent apoptosis in human ovarian cancer cells

Abstract: Resveratrol is a naturally occurring trihydroxyl-diphenylethylene compound that has been shown experimentally to have beneficial effects in the treatment of cancer and cardiovascular disease. Resveratrol induces programmed cell death (apoptosis) in these cells and activates important signal transducing proteins including extracellular signal-regulated kinases (ERKs) 1 and 2 in cancer cells. Resveratrol also causes nuclear accumulation of the enzyme cyclooxygenase (COX)-2 and of the oncogene suppressor protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 55 publications
6
57
0
Order By: Relevance
“…Several studies have previously demonstrated marked antitumor activities of resveratrol against various ovarian cancer cells. Resveratrol has been shown to inhibit both the growth and proliferation of human ovarian cancer cells, such as OVCAR-3, PA-1 and SKOV-3, through induction of apoptosis, DNA damage and S-phase arrest (Yang et al, 2003;Tyagi et al, 2005;Raj et al, 2008;Lee et al, 2009;Björklund et al, 2011;Lin et al, 2011;Marimuthu et al, 2011). Resveratrol induced cell death and growth inhibition in A1947, A2780, CaOV3, ES-2, SKOV3 and TOV112D cells by autophagocytosis and inhibition of glycolysis (Opipari et al, 2004;Kueck et al, 2007).…”
Section: 1333 Resveratrol Effects On Ovarian Cancer Cells Differ In mentioning
confidence: 99%
“…Several studies have previously demonstrated marked antitumor activities of resveratrol against various ovarian cancer cells. Resveratrol has been shown to inhibit both the growth and proliferation of human ovarian cancer cells, such as OVCAR-3, PA-1 and SKOV-3, through induction of apoptosis, DNA damage and S-phase arrest (Yang et al, 2003;Tyagi et al, 2005;Raj et al, 2008;Lee et al, 2009;Björklund et al, 2011;Lin et al, 2011;Marimuthu et al, 2011). Resveratrol induced cell death and growth inhibition in A1947, A2780, CaOV3, ES-2, SKOV3 and TOV112D cells by autophagocytosis and inhibition of glycolysis (Opipari et al, 2004;Kueck et al, 2007).…”
Section: 1333 Resveratrol Effects On Ovarian Cancer Cells Differ In mentioning
confidence: 99%
“…It was also remarkable that the receptors for thyroid hormone and for resveratrol did not appear to interact functionally with one another. That is, both agents activated intracellular pools of MAPK (ERK1/2), but resveratrol was pro-apoptotic (Lin H et al, 2008a;Lin C et al, 2011) whereas thyroid hormones (T 4 , T 3 ) were anti-apoptotic (Lin H et al, 2008b), as noted above. Such observations suggested that the results of any efficacy testing of resveratrol as a chemotherapeutic agent in the presence of physiologic concentrations of thyroid hormone in vitro or in the intact animal with a normal pituitary-thyroid axis may be difficult to interpret (see below).…”
Section: Actions Of Resveratrol and The Integrin Receptor On The Biolmentioning
confidence: 90%
“…An Arg-Gly-Asp (RGD) peptide prevents both the pro-apoptotic activity of resveratrol and the anti-apoptotic activity of thyroid hormone, indicating that the receptor is near the RGD recognition site on the integrin that was mentioned above (see section on Thyroid Hormone Action). The interactions of tetrac with either T 4 or resveratrol, however, indicate that the two integrin binding sites are distinct, in that while tetrac inhibits the proliferative action of T 4 in cancer cells, tetrac does not inhibit the pro-apoptotic actions of resveratrol (Lin C et al, 2011). Our own studies of the mechanism by which resveratrol may act to induce apoptosis in tumor cells have revealed several unexpected findings.…”
Section: Actions Of Resveratrol and The Integrin Receptor On The Biolmentioning
confidence: 96%
See 1 more Smart Citation
“…Resveratrol activates ERK1/2 at low concentrations (1 pM-10 μM), but at higher concentrations (50-100 μM) can inhibit MAPK in human neuroblastoma SH-SY5Y cells [142]. In contrast, resveratrol activates ERK1/2 in prostate [143], breast [144,145], glial [146], head and neck [147], and ovarian cancer cells [148]. MAPKs in a constitutively active state are necessary to maintain the malignant state; however, short-term activation of MAPK may drive the cells to apoptosis [149].…”
Section: Anti-tumor-promotion Activitymentioning
confidence: 99%